Antiproliferative Activity of Microalgal Extracts on Nasopharyngeal Carcinoma (NPC) Cells - Lai, P. J.; Chu, W. L.; Naidul, R.; Khoo, A. S. B.; Kok, Y. Y.; M. M, Shar; Ling, S. N.; Mak, J. W.; Lim, K. C.; Balraj, P.; Phalle, S. M. (Malaysian Journal of Science, 2008)
Nasopharyngeal carcinoma (NPC) is a type of epithelial neoplasms arising from the nasopharynx. The disease is frequently encountered in southern China, Taiwan and Hong Kong. Algae are known to be a potential source of bioactive compounds with antiproliferative activity on cancer cells. The objective of this study was to screen extracts of microalgae from the University of Malaya Algae Culture Collection (UMACC) for antiproliferative activity against NPC cell lines. Solvent and aqueous extracts of 19 microalgae from the UMACC were screened for antiproliferative activity on four NPC cell lines, namely CNE1, HONE1, TWO1 and TWO4. The methanol extracts from two microalgae, namely Ankistrodesmus convolutus UMACC 101 and Synechococcus elongatus UMACC 105 showed antiproliferative activity on the NPC cell lines, with IC50 values ranging from 95.7 to 98.0ptg/mL. The methanol extract from Synechococcus elongatus was subjected to fractionation by column and thin layer chromatography (TLC) using a combination of hexane and acetone at different ratios. Fraction 7’ obtained from the pooled eluents of 6:4, 5:5, 4:5 and 3:7 hexane-acetone was the most active, with IC50 values of 10.2 and 4.8 ptg/mL on CNE1 and TWO4 cells respectively. The cytotoxic effect of Fraction 7’was evident against CNE1 and TWO4 cells after 24 and 48h respectively at 30.0 ptg/mL. The mechanism of action of Fraction 7’ could be through induction of apoptosis as indicated by the increased percentage of cells in the Sub-GO phase in cell cycle analysis by flow cytometry. The active compound in Fraction 7’ could be a derivative product of chlorophyll a, as indicated by the blackish green spot after separation by TLC. Further studies are warranted to elucidate the structure of the active principle in Fraction 7’.